Corrosion Resistance of Strain Hardening Fiber Reinforced Cementitious Composites - Ahmed, Shaikh (Nova Science Publishers, Inc., 2011)
Deterioration of reinforced concrete (RC) structures due to corrosion of reinforcing steel is recognized as a major problem worldwide. In RC structures the corrosion initiates due to the penetration of aggressive substances through pores and existing cracks in the cover concrete. The cracks in RC structures form due to load and/or environmental effects (shrinkage and thermal) during their service life. Because of the expansive corrosion reaction and low strain capacity and fracture resistance of concrete, spalling and delamination of the cover concrete eventually occur, often resulting in loss of load carrying and deflection capacity of the structure. This chapter presents the state-of-the-art on corrosion resistance of strain hardening fiber reinforced cementitious composites (SHFRCC) that exhibit strain hardening and multiple cracking behaviours in tension and bending. The SHFRCC is cement based short and discrete fiber reinforced composites. Superior corrosion resistance of RC beams containing SHFRCC is observed over RC beams made with conventional concrete. The SHFRCC is also found to be effective in preventing the corrosion-induced damage in RC beams. The better performance of the RC beam containing SHFRCC is also evident from the absence of any corrosion-induced cracking and the very low tendency of the concrete cover to delaminate.